The Effect Of Probiotic Isolated From Black Tiger Shrimp (Penaeus monodon Fab) In Artificial Feed On Growth And Feed Efficiency Of Baung (Hemibagrus nemurus) - Erica Silvia; Indra Suharman; adelina adelina (Berkala Perikanan Terubuk, 2016)
This research aimed to determine the effect of addition probiotic isolated from Black Tiger Shrimp (Penaeus monodon Fab.) in artificial feed on feed digestibility, feed efficiency, protein retention and growth of baung (Hemibagrus nemurus). The research used a Complete Randomized Design (RAL), it was used with one factor, four treatments and three replications. The treatments are : P0 (no addition of probiotic), P1 (5 ml/kg feed), P2 (10 ml/kg feed), P3 (15 ml/kg feed). The result showed that the effects of probiotic that isolated from Black Tiger Shrimp into the artificial feed was  affected of the growth rate and feed efficiency of baung. the best treatment contained in P2 (10 ml/kg feed) that showed Feed digestibility at 64,92 %, feed efficiency at 38,12%, protein retention at 67,52%, and specific growth rate 3,40%.